INVESTIGATION OF STRESS-CORROSION CRACKING OF HIGH-STRENGTH ALLOYS - AEROJET-GENERAL CORP AZUSA CA (1961)
Bent-beam stress-corrosion test data are presented for 9 of the 11 environments on Vascojet 1000 and Ladish D6AC alloy steels, AM355 stainlees steel, and B12OVCA Ti alloy. The average air temperature was 73 F and the average relative humidity was 52%. Very few failures occurred with the bent- beam type specimens. U-bend test specimens are being prepared for conducting environmental stress-corrosion tests to provide supplemental data to the bent- beam tests.AD-2594 9N6 AD-259 437Div. 2 (17 July 61) OTS price $3.60 Weather Forecasting Research Center, U. of Chicago, Ill. A CONTRIBUTION TO THE CLIMATOLOGY OF THE ARCTIC STRATOSPHERE. by E. Paul McClain. Feb 61, 32p. incl. illus. tables, 27 refs. (Scientific rept. no. 3) (Contract AF 19(604)7230) (AFCRL-612)Unclassified report DESCRIPTORS: *Stratosphere, Arctic regions, Climatic factors, Meteorological data, temperature inversion, Statistical distribu tions, *Climate, *Weather forecasting, Statistical analysis, Temperature, Measure ment. A previous study of January temperatures in the mid-stratosphere at several arctic stations near 80W was extended to include other stations in the North American, European and Asiatic sectors of the Arctic and to the remaining 2 months of the winter season. Distinctly bimodal temperature frequency distributions are evidently confined to the general area of the Canadian Archipelago and northern Greenland, being characteristic of this region throughout the winter. Mean 25-mb charts and mean cross-sections are used to illustrate the 2 quite dissimilar thermal and circulation regimes that tend to dominate the arctic stratosphere for long periods during the polar night.